Distinction in anodic dissolution behavior on different planes of laser solid formed Ti-6Al-4V alloy. (1st September 2018) - Li, Jiaqiang; Lin, Xin; Zheng, Min; Wang, Jian; Guo, Pengfei; Qin, Tuo; Zhu, Minghui; Huang, Weidong; Yang, Haiou
Abstract: Microstructure, electrochemical impedance, and Tafel and potentiodynamic polarizations were characterized to investigate the electrochemical anodic dissolution behavior of Ti-6Al-4V alloy produced by the laser solid forming (LSF) additive manufacturing process with a specific focus on the distinction on different planes. Electrochemical measurements show that the anodic dissolution characteristic of LSFed Ti-6Al-4V reveals anisotropic behavior on different planes. The horizontal-plane (XOY plane) is more resistant to corrosion than the vertical-plane (XOZ plane) in 15 wt% NaCl solution. Additionally, the vertical-plane shows a lower initial machining potential for the process of electrochemical machining compared to the horizontal-plane. The microstructure of Ti-6Al-4V alloy deposit is composed of dominant α-laths and small amounts of β phase, and its horizontal-plane has higher content of the β phase, lower content of the α phase, slightly finer α-laths, and more uneven α-lath width distribution compared to the vertical-plane. These differences in the microstructural characteristics produce the distinctions observed in the electrochemical anodic dissolution behavior of LSFed Ti-6Al-4V alloy on the vertical- and horizontal-planes.